Hierarchical Multiporous Nickel for Oxygen Evolution Reaction in Alkaline Media. Issue 24 (22nd October 2019) - Assavapanumat, Sunpet; Ketkaew, Marisa; Garrigue, Patrick; Lapeyre, Véronique; Reculusa, Stéphane; Wattanakit, Chularat; Kuhn, Alexander
Abstract: Electrochemical water splitting is a crucially important process for energy conversion and storage. In this context, we report the synthesis of hierarchical multiporous nickel nanosheets obtained by a templated two‐step electrodeposition of nickel in the presence of silica beads and an assembly of nonionic surfactant in order to generate a combined macro‐ and mesoporous structure. Interestingly, the synergistic effect of these highly ordered meso‐ and macroporous structures promotes the catalytic performance for oxygen evolution reaction with one order of magnitude higher current densities and a better stability of the electrodes compared to flat nickel or electrodes having a single type of porosity. This example illustrates a promising strategy for the rational design of high‐performance porous metals, not only in the frame of water electrolysis, but also for other electrocatalytic applications. Abstract : Electrocatalysis : Highly organized hierarchical porous nickel has been obtained by combining a hard‐ and soft‐template method in order to increase its electrocatalytic performance and stability during oxygen evolution reaction